Review on the Development and Applications of Medicinal Plant Genomes - Cheng, Qi-Qing; Ouyang, Yue; Tang, Zi-Yu; Lao, Chi-Chou; Zhang, Yan-Yu; Cheng, Chun-Song; Zhou, Hua (Frontiers in Plant Science, 2021)
With the development of sequencing technology, the research on medicinal plants is no longer limited to the aspects of chemistry, pharmacology, and pharmacodynamics, but reveals them from the genetic level. As the price of next-generation sequencing technology becomes affordable, and the long-read sequencing technology is established, the medicinal plant genomes with large sizes have been sequenced and assembled more easily. Although the review of plant genomes has been reported several times, there is no review giving a systematic and comprehensive introduction about the development and application of medicinal plant genomes that have been reported until now. Here, we provide a historical perspective on the current situation of genomes in medicinal plant biology, highlight the use of the rapidly developing sequencing technologies, and conduct a comprehensive summary on how the genomes apply to solve the practical problems in medicinal plants, like genomics-assisted herb breeding, evolution history revelation, herbal synthetic biology study and geoherbal research, which are important for effective utilization, rational use and sustainable protection of medicinal plants.